2020
DOI: 10.1136/jitc-2019-000415
|View full text |Cite|
|
Sign up to set email alerts
|

A new oncolyticVacciniavirusaugments antitumor immune responses to prevent tumor recurrence and metastasis after surgery

Abstract: BackgroundLocal recurrence and remote metastasis are major challenges to overcome in order to improve the survival of patients with cancer after surgery. Oncolytic viruses are a particularly attractive option for prevention of postsurgical disease as they offer a non-toxic treatment option that can directly target residual tumor deposits and beneficially modulate the systemic immune environment that is suppressed post surgery and allows residual disease escape from control. Here, we report that a novelVaccinia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…We have previousl demonstrated that a TK-deleted, N1L-deleted VV has potent efficacy and tumor selectivity in vivo 13 14 ( online supplemental figure S1 ). To maximize the oncolytic potential of VV, we enhanced the capacity for systemic spread by increasing EEV production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previousl demonstrated that a TK-deleted, N1L-deleted VV has potent efficacy and tumor selectivity in vivo 13 14 ( online supplemental figure S1 ). To maximize the oncolytic potential of VV, we enhanced the capacity for systemic spread by increasing EEV production.…”
Section: Resultsmentioning
confidence: 99%
“…NK cells play a critical role in the elimination of MHCI-deficient tumors that may otherwise evade immune surveillance. We previously demonstrated that modulation of the VV backbone by deletion of the N1L gene could enhance systemic NK cell responses and prevent postsurgical tumor recurrence in murine models of pancreatic, lung and breast cancer 13 and IL-21 is able to increase these responses further. Interestingly, Seo et al recently reported a critical role for IL-21 in the reversal of NK cell exhaustion, common to MHCI-deficient tumors, 46 thus further phenotypic examination of the NK populations induced by VVL-21 is warranted in future experiments, although based on our results, this can reasonably be expected to extend to our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of an OV in combination with inhibition of transforming growth factor-β signaling is thought to increase the efficacy of immunotherapy ( 42 ). According to a recent study, a novel Vaccinia virus known as VVΔTKΔN1L , with thymidine kinase and N1L gene deletions and armed with interleukin 12, successfully prevented the recurrence of tumors in surgical models of head and neck cancer in Syrian hamsters ( 46 ). This study laid an important experimental foundation for the development of new drugs in the treatment of solid tumors.…”
Section: Immunotherapymentioning
confidence: 99%
“… 20 , 21 We have recently reported that an additional deletion of the VV 13.8-kDa N1L protein, a neurovirulence factor, 22 can further increase the safety profile of the virus (named VVLΔTKΔN1L) and enhance anti-tumor immune responses, particularly adaptive CD8 + T cell and innate natural killer (NK) cell responses, consequent to viral infection, resulting in superior anti-tumor efficacy of VVLΔTKΔN1L compared to VVLΔTK in a number of in vivo murine and hamster models of cancer. 23 …”
Section: Introductionmentioning
confidence: 99%